2022
DOI: 10.1002/mp.15642
|View full text |Cite
|
Sign up to set email alerts
|

3D computational model of oxygen depletion kinetics in brain vasculature during FLASH RT and its implications for in vivo oximetry experiments

Abstract: Ultra-high-dose-rate irradiation, also known as FLASH, has been shown to improve the therapeutic ratio of radiation therapy (RT). The mechanism behind this effect has been partially explained by the radiochemical oxygen depletion (ROD) hypothesis, which attributes the protection of the normal tissue to the induction of transient hypoxia by ROD. To better understand the contribution of oxygen to the FLASH effect, it is necessary to measure oxygen (O 2 ) in vivo during FLASH irradiation. This study's goal is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…It is possible to obtain the oxygen depletion solution within a realistic tissue/vasculature 3D space with finite element method. Cui and Pratx ( 84 ) provided an example of mesh in 3D vasculature space in a mouse brain and worked on oxygen level recovery after the irradiation. To extend our current work into 3D vasculature space, it is imperative to perform the simulation on a representative collection of the animal tumor and normal tissue vasculature models to derive statistically meaningful results for FLASH sparing effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to obtain the oxygen depletion solution within a realistic tissue/vasculature 3D space with finite element method. Cui and Pratx ( 84 ) provided an example of mesh in 3D vasculature space in a mouse brain and worked on oxygen level recovery after the irradiation. To extend our current work into 3D vasculature space, it is imperative to perform the simulation on a representative collection of the animal tumor and normal tissue vasculature models to derive statistically meaningful results for FLASH sparing effects.…”
Section: Discussionmentioning
confidence: 99%
“…developed a 3D computation model to measure oxygen in vivo during FLASH‐RT. They concluded that the process on the order of milliseconds is recommended for radiochemical oxygen depletion measurements in normal tissues 28 . Rothwell et al.…”
Section: The Mechanism For Flash Effectmentioning
confidence: 99%
“…They concluded that the process on the order of milliseconds is recommended for radiochemical oxygen depletion measurements in normal tissues. 28 Rothwell et al. presented their modeling work about oxygen depletion by implanted biological, radiochemical, and delivery parameters.…”
Section: The Mechanism For Flash Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…For CDR radiation, this depletion occurs slowly, and the loss of oxygen is counteracted by replenishment through diffusion from the vasculature. In contrast, UHDR radiation is rapid enough to induce a transient and measurable drop in the local concentration of oxygen in the irradiated tissues [14,15], which has the potential to alter radiobiological responses [18][19][20][21]. In addition, a second reason is that changes in oxygen levels within the irradiated tis-sues have been shown to modulate the ability of UHDR radiation to spare normal tissues, a clear indication that oxygen is involved in mediating the FLASH effect [8][9][10][22][23][24].…”
mentioning
confidence: 99%